Vegetative Propagation of Ochreinauclea missionis (wall. Ex G. Don) Ridsd. a Rare and Threatened Tree Species of Western Ghats - Jose, P. A.; Thomas, Jacob; Krishnan, P. N. (Indian Forester, 1995)
Ochreinauclea missionis (Wall ex G. Don) Ridsd. is an extremely rare and threatened medicinally important tree, endemic to Western Ghats. Vegetative propagation of the plant was tried using stem cuttings treated with auxins (IAA, IBA and NAA) during summer, monsoon months and air layering in order to develop promising propagation methods to aid for its conservation. Soft cuttings treated with IBA at a concentration of 1000 ppm during monsoon and air layering during August-October were found to be ideal methods of vegetative propagation of the species.